The future potential of virtual reality countermeasures for maintaining behavioural health during long duration space exploration - Thomas, Laura J. (Frontiers in Virtual Reality, 2023)
Long duration space exploration is no longer a fantasy, with Elon Musk claiming to launch astronauts to Mars as early as 2029. The substantial increase in spaceflight duration required for a Mars mission has resulted in a stronger focus on behavioural health outcomes at NASA, with increased interest in using virtual reality countermeasures to both monitor and promote psychological wellbeing. From the perspective of a practitioner psychologist, this paper first considers the utility of virtual reality assessment of emerging behavioural health concerns for remote monitoring purposes. Key opportunities include using virtual reality for functional cognitive testing and leveraging the predictive abilities of multimodal data for personalised insights into symptomology. Suggestions are given as to how astronauts can self-monitor usage of virtual leisure activities that facilitate positive emotional experiences. Secondly, the potential to develop virtual reality countermeasures to deliver semi-structured therapeutic interventions such as collaborative cognitive-behavioural formulation in the absence of real-time communication is discussed. Finally, considerations for the responsible implementation of psychological monitoring tools are reviewed within a context of fostering psychological safety and reducing stigma.